Comanagement With Nephrologist Care Is Associated With Fewer Cardiovascular Events Among Liver Transplant Recipients With Chronic Kidney Disease - Patrick T. Campbell, MD (Transplantation Direct, 2021)
Background. Chronic kidney disease (CKD) is associated with cardiovascular (CV) events, a leading complication in liver transplant recipients (LTRs). Timely subspecialty care is associated with improved clinical outcomes in patients with CKD. This study sought to assess associations between nephrology comanagement and CV events among LTRs at risk for or with CKD. Methods. LTRs with CKD plus those at risk were identified in an inception cohort at a single tertiary care network between 2010 and 2016, using electronic health record data and manual chart review. CKD was defined as estimated glomerular filtration rate <60 mL/min/1.73 m2 or International Classification of Diseases 9th or 10th revision code for CKD and at-risk CKD as estimated glomerular filtration rate 60–89 mL/min/1.73 m2. Cox proportional hazard models assessed the association between nephrology comanagement and CV events among LTRs with or at risk for CKD. Results. Among 602 LTRs followed for up to 6 y posttransplant, prevalence of CKD plus those at risk increased yearly (71% in year 1, 86% in year 6) (P < 0.0001). Rates of nephrology comanagement decreased yearly posttransplant (35% in year 1, 28% in year 6). In multivariable models, nephrology comanagement was associated with lower CV events (adjusted hazard ratio, 0.57; 95% confidence interval, 0.33–0.99). Conclusions. Among LTRs with CKD, nephrology comanagement may be associated with lower CV events. A prospective study is needed to identify the reasons for improved outcomes and barriers to nephrology referral.